Poly (phenyl sulfone)/graphite composite as a robust low-cost, comb-type interdigited sensor for detection of organic solvent vapors - Sakar Dasdan, Dolunay (SPRINGER, 2021)
An approach for quantitative detection of organic vapors is demonstrated. Herein, an interdigited electrode was fabricated by drop casting of graphite loaded poly(phenyl sulfone) (PPSU/Gr) film on a conductive substrate. The sensor is experimentally tested on several organic solvents including alkanes, acetates, aromatic hydrocarbons and chloroform via electrical resistance measurements and inverse gas chromatography (IGC) method. Relationships between the sensor response (as obtained by electrical resistance) and solvent properties such as polarity, acidity and partition coefficient (as obtained from IGC) are established. Moreover, the surface dispersive free energy of PPSU and PPSU/Gr were calculated according to both Dorris-Gray and Schultz equations, it is found that with the addition of graphite to PPSU the surface dispersive free energy of PPSU at 25 degrees C decreased from 28 to 10 mJ m(-2) (from Dorris Gray approach) and from 25 to 17 mJ m(-2) (from Schultz approach), suggesting higher interfacial area for exposed gases at PPSU/Gr sensor. Furthermore, the PPSU/Gr modified electrode exhibited high sensitivity towards chlorinated hydrocarbons. Importantly, the PPSU/Gr electrode showed good mechanical stability, low response time, and is costly-effective and disposable, rendering it a promising sensor for gases detection.
Keywords: Poly (phenyl sulfone); Graphite; Conductive composites; Solvent vapor sensor; Partition coefficient; Gas sensor; Polymer Science